1997
DOI: 10.1177/159101999700300303
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Management of Paediatric Intracranial Aneurysms

Abstract: The purpose of this paper is to discuss the radiological and clinical features of paediatric intracranial aneurysms including endovascular techniques currently being used for their therapy. Paediatric patients who presented with the diagnosis of intracranial aneurysm between August 1982 and February 1997 were included. The data were collected retrospectively. Clinical features included patient's age, sex, presentation, treatment and outcome. Radiologic features included location, siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 19 publications
0
21
0
2
Order By: Relevance
“…This increase in coil embolization compared with surgical clipping operations may be due to the observed good outcome rates associated with coil embolization in previous studies. 1,6,8,15,16,20 This study has several limitations. First and foremost, we were unable to address information about aneurysm morphology, anatomical location, and other clinical characteristics such as the clinical grade that might affect decision making in selecting the type of treatment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This increase in coil embolization compared with surgical clipping operations may be due to the observed good outcome rates associated with coil embolization in previous studies. 1,6,8,15,16,20 This study has several limitations. First and foremost, we were unable to address information about aneurysm morphology, anatomical location, and other clinical characteristics such as the clinical grade that might affect decision making in selecting the type of treatment.…”
Section: Discussionmentioning
confidence: 97%
“…There has been no similar clinical trial to compare these treatment options in children. Although there are observational studies addressing the efficacy and safety of endovascular coiling and clipping in children, 1,14,16,27 the largest study included only 33 patients with 37 aneurysms, which showed better clinical outcomes associated with coiling compared with clipping. 1 Because of the lack of evidence in children with intracranial aneurysms, and because of the small sample size in most published series, we sought to evaluate these treatment options in a large sample abstracted from a national database.…”
Section: ©Aans 2014mentioning
confidence: 99%
“…This does not have a bearing on the clinical condition or development of delayed ischemic neurologic deficits, however [8,14] , and children generally tolerate vasospasm well. In our series, the incidence of angiographic vasospasm was 16.3%, but there was no clinical evidence of spasm and all had excellent outcomes, with the probable explanation being the robust leptomeningeal collaterals in children and the ability of the young brain to withstand ischemic insult [1,7,17] . Ischemic insult due to vasospasm was seen in 27% our adult cases.…”
Section: Discussionmentioning
confidence: 58%
“…ICA bifurcation aneurysms were seen in only 3.8% of the cases in adults. Posterior circulation aneurysms occur more commonly in children than in adults (up to 3 times more common) [15] ; they can be seen in about 24-39% of children [1,17] and 5.5-8% of adults [2,4] . They were seen in 9.1% of our pediatric cases.…”
Section: Discussionmentioning
confidence: 99%
“…ie Pr~tvalenz intrakranieller Aneurysmen bei Kindern betr~igt 0,5 bis 4,6% [7,13], wobei die j~ihrli-che Inzidenz von aneurysmatischer Subarachnoidalblutung 1 : 100000 (Erwachsene 10:100000)betr~gt. 13,5 bis 24% der Aneurysmen rinden sich im posterioren Stromgebiet [10] (Erwachsene 5%).…”
unclassified